2019
DOI: 10.1002/ijc.32650
|View full text |Cite
|
Sign up to set email alerts
|

Searching for prognostic biomarkers for small renal masses in the urinary proteome

Abstract: Renal cell carcinoma (RCC) is frequently diagnosed incidentally as an early‐stage small renal mass (SRM; pT1a, ≤4 cm). Overtreatment of patients with benign or clinically indolent SRMs is increasingly common and has resulted in a recent shift in treatment recommendations. There are currently no available biomarkers that can accurately predict clinical behavior. Therefore, we set out to identify early biomarkers of RCC progression. We employed a quantitative label‐free liquid chromatography coupled to tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…COAD is the most common intestinal tumor worldwide, especially in women ( Hassanlou et al, 2019 ), and has been reported to be associated with many oncogenes ( Yin et al, 2017 ). Existing literature reports CCT6A to possess oncogenic features in a various human cancer ( Di Meo et al, 2019 ; Huang et al, 2019 ). This study of bioinformatics analysis of publically available genetic sequencing data was performed to gain further insight into the role of CCT6A in the genetic regulation of COAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COAD is the most common intestinal tumor worldwide, especially in women ( Hassanlou et al, 2019 ), and has been reported to be associated with many oncogenes ( Yin et al, 2017 ). Existing literature reports CCT6A to possess oncogenic features in a various human cancer ( Di Meo et al, 2019 ; Huang et al, 2019 ). This study of bioinformatics analysis of publically available genetic sequencing data was performed to gain further insight into the role of CCT6A in the genetic regulation of COAD.…”
Section: Discussionmentioning
confidence: 99%
“… Ma et al (2018) showed that CCT6A was involved in the proteogenomic characterization of human colorectal cancer liver metastasis. Di Meo et al (2019) reported that CCT6A was a potential prognostic biomarker in renal cell carcinoma. Klimczak et al (2019) also suggested that CCT6A may be involved in imparting an unfavorable prognosis in breast cancer tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate peptides for 23 proteins were selected using the online comprehensive platforms, Selected Reaction Monitoring Atlas (SRMAtlas) [ 35 ] and neXtProt [ 36 ], which combine peptide information with MS-observed evidence. The peptide selection was based on certain criteria, as previously described [ 37 , 38 ]. In the end, one to two tryptic peptides per protein that showed a satisfactory chromatographic spectrum in Skyline (v.19.1.0.193) were selected for PRM method development (Additional file 1 : Table S5).…”
Section: Methodsmentioning
confidence: 99%
“…In TBSRTC DC4 nodules, CCT6A-AAbs were capable of detecting borderline and malignant tumors with DSp and DSn values of 100% and 40%, respectively [ 125 ]. Interestingly, more recent studies extensively implicated TCP-1ζ/CCT6A as an oncogenic protein and biomarker of poor prognosis in various human malignancies [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ], rendering its cancer-associated immunogenicity highly biologically relevant.…”
Section: The Tumor-associated Antigens (Taas) and Their Cognate Autoa...mentioning
confidence: 99%